2008
DOI: 10.1002/adsc.200800198
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Marine Oxylipins Solandelactones A–H

Abstract: The Solandelactones A-H have been synthesized via a short convergent approach utilizing common building blocks. Based on the diastereoselectivity of the crucial final addition step and on the comparison of prominent NMR data, a structural revision was necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
25
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…The major alcohol 142 in this case corresponded spectroscopically with (11S)-solandelactone A and the minor alcohol 143 with (11R)-solandelactone B, requiring Shin's C11 assignment to the A/B pair as well as the E/F pair to be reversed. On this basis, it seemed likely that Shin's assignment to C11 configuration of the remaining C/D and G/H pairs of solandelactones should be reversed, and very recently Pietruszka completed a synthesis of all eight solandelactones A-H which confirmed this 63. Solandelactones A-D would logically originate in nature from docosatetraenoic acid 144 via the pathway shown in Scheme 25.…”
mentioning
confidence: 74%
“…The major alcohol 142 in this case corresponded spectroscopically with (11S)-solandelactone A and the minor alcohol 143 with (11R)-solandelactone B, requiring Shin's C11 assignment to the A/B pair as well as the E/F pair to be reversed. On this basis, it seemed likely that Shin's assignment to C11 configuration of the remaining C/D and G/H pairs of solandelactones should be reversed, and very recently Pietruszka completed a synthesis of all eight solandelactones A-H which confirmed this 63. Solandelactones A-D would logically originate in nature from docosatetraenoic acid 144 via the pathway shown in Scheme 25.…”
mentioning
confidence: 74%
“…Misassignments of single stereocenters (Table 7) near to correctly assigned centers are associated with interpretation of NOE data for structurally diverse compounds. For example, this is the case for brevenal, 61, 62 solandelactones A-H, 63, 64 ritterazines B 65, 66 and F, 67 netamines E and G, 68, 69 briarellin J, 70, 71 and dictyosphaeric acid A. 72, 73 Consideration of the source of these errors highlights the need for careful evaluation of all possible alternative molecular models that adhere to NOE constraints.…”
Section: Sources Of Natural Product Structural Misassignmentsmentioning
confidence: 99%
“…[3] Initial assignment of structure and absolute stereochemistry was based primarily on NMR studies, which led to two sets of compounds depending on their configuration at C11: R configuration for A, C, E, and G; S configuration for B, D, F, and H. However, the experimental data for synthetic solandelactone "F", which had been synthesized by Martin and coworkers, [4] matched the data for solandelactone E, thus indicating that the two sets of compounds had been incorrectly assigned. Further syntheses by White et al [5] as well as Pietruszka and Rieche [6] confirmed that the configuration at C11 in all of the solandelactones A-H should be depicted as in Scheme 1.…”
mentioning
confidence: 85%
“…In fact, it has been shown that the configuration at C11 ( % 2:1) is controlled predominantly by the configuration at C14 and not by the configuration of the cyclopropane ring. [6,9] Martins synthesis provides a unique strategy to access this class of compounds, which features high levels of stereocontrol. [4] His strategy avoids the C11-C12 disconnection but this inevitably makes the synthesis more linear.…”
mentioning
confidence: 99%
See 1 more Smart Citation